2009
DOI: 10.1007/s10853-009-3368-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and microstructures of Pd-free Ag–Au–Pt–Cu dental alloys

Abstract: Nine experimental Pd-free Ag-Au-Pt-Cu dental alloys containing 10 at.% Pt and 10 to 35 at.% Au were prepared and their optical properties and microstructures were investigated by means of spectrophotometric colorimetry, optical microscopy, and electron probe microanalysis. All the alloys were annealed at 850°C and mirror-polished to observe their reflectance curves in the visible spectrum and three-dimensional color coordinates. All the alloys were composed of a major phase of Ag-Au-rich matrix and a minor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
3
7
2
Order By: Relevance
“…The higher reflectance for high wavelengths exhibited by alloys A, B and C are in agreement with Shiraishi et al [29] findings for gold alloys with high gold content. The same authors showed that the three pure elements composing these alloys, i.e.…”
Section: Hardnesssupporting
confidence: 92%
See 2 more Smart Citations
“…The higher reflectance for high wavelengths exhibited by alloys A, B and C are in agreement with Shiraishi et al [29] findings for gold alloys with high gold content. The same authors showed that the three pure elements composing these alloys, i.e.…”
Section: Hardnesssupporting
confidence: 92%
“…The L* value registered for the different samples did not significantly differ within each group, ranging from ∼55 to ∼59. These luminance values are relatively lower than those reported by Shirishi et al [29], but such differences are related to colour measuring experimental set up, particularly with the reduced area of the samples that was used for measuring the colour.…”
Section: Hardnesscontrasting
confidence: 69%
See 1 more Smart Citation
“…According to the authors' previous study using electron probe microanalysis, it was found that the matrix was rich in Ag and Au while the secondphase small grains were rich in Pt and Cu 10) . The PtCu-rich second-phase grains were well protected from the tarnish attack in all the samples, as shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study, the chemical compositions of the matrix and second-phase small grains in alloy C were determined by EPMA 24) . The matrix was rich in Ag and Au, whereas the second-phase small grains were rich in Pt and Cu 24) . In this study, only the Ag-Au-rich matrix was corroded after the CV forward scan (Figs.…”
Section: Factors Controlling the Corrosion Resistance Of Ag-au-pt-cu mentioning
confidence: 99%